Between the bench, the bedside and the office: The need to build bridges between working neuroscientists and ethicists. (December 2014) - Brosnan, Caragh; Cribb, Alan
This paper presents findings from an empirical study that explored the meaning of ethics in the everyday work of neuroscientists. Observation and interviews were carried out in one neuroscience research group that was involved in bench-to-bedside translational research. We focus here specifically on the scientists' perceptions of bioethics. Interviewees were often unfamiliar with bioethics as a discipline, particularly the more junior members of the group. Those who were aware of its existence largely viewed it as something distant from them, and as either too abstract, not relevant or an alien imposition on their work. Some interviewees themselves pointed to the need for better 'bridge building' between ethical principles and real-world examples drawn from scientific practice, and we argue that this space is where a more empirically grounded ethics may be useful in terms of actually engaging scientists at both the bench and the bedside.